The K2-HERMES Survey: age and metallicity of the thick disc. Issue 4 (12th October 2019) - Sharma, Sanjib; Stello, Dennis; Bland-Hawthorn, Joss; Hayden, Michael R; Zinn, Joel C; Kallinger, Thomas; Hon, Marc; Asplund, Martin; Buder, Sven; De Silva, Gayandhi M; D'Orazi, Valentina; Freeman, Ken; et al.
ABSTRACT: Asteroseismology is a promising tool to study Galactic structure and evolution because it can probe the ages of stars. Earlier attempts comparing seismic data from the Kepler satellite with predictions from Galaxy models found that the models predicted more low-mass stars compared to the observed distribution of masses. It was unclear if the mismatch was due to inaccuracies in the Galactic models, or the unknown aspects of the selection function of the stars. Using new data from the K2 mission, which has a well-defined selection function, we find that an old metal-poor thick disc, as used in previous Galactic models, is incompatible with the asteroseismic information. We use an importance-sampling framework, which takes the selection function into account, to fit for the metallicities of a population synthesis model using spectroscopic data. We show that spectroscopic measurements of [Fe/H] and [α/Fe] elemental abundances from the GALAH survey indicate a mean metallicity of log ( Z/Z ⊙ ) = −0.16 for the thick disc. Here Z is the effective solar-scaled metallicity, which is a function of [Fe/H] and [α/Fe]. With the revised disc metallicities, for the first time, the theoretically predicted distribution of seismic masses show excellent agreement with the observed distribution of masses. This indirectly verifies that the asteroseismic mass scaling relation is good to within five per cent. Assuming the asteroseismic scaling relations are correct, we estimate the mean age of the thick disc to be about 10 Gyr, in agreement with the traditional idea of an old α-enhanced thick disc.